2016
DOI: 10.5492/wjccm.v5.i1.83
|View full text |Cite
|
Sign up to set email alerts
|

Critical care of obese patients during and after spine surgery

Abstract: Obesity is one of the most prevalent health problems facing the United States today, with a recent JAMA article published in 2014 estimating the prevalence of one third of all adults in the United States being obese. Also, due to technological advancements, the incidence of spine surgeries is growing. Considering these overall increases in both obesity and the performance of spinal surgeries, it can be inferred that more spinal surgery candidates will be obese. Due to this, certain factors must be taken into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[17][18][19][20][21][22][23] Furthermore, morbidly obese patients tend to have poorer quality of preoperative imaging, increased difficulty during the surgical approach due to excess subcutaneous fat deposits, and enhanced difficulty in intraoperative anesthetic management. 14,24,25 Not surprisingly, many studies have shown a significantly higher rate of perioperative complications in morbidly obese patients. 15,26,27 Recent advances in anesthetic and surgical management, however, have made PLF an increasingly viable and safe option for morbidly obese patients, and the rate of spinal surgery in this patient population has risen in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Furthermore, morbidly obese patients tend to have poorer quality of preoperative imaging, increased difficulty during the surgical approach due to excess subcutaneous fat deposits, and enhanced difficulty in intraoperative anesthetic management. 14,24,25 Not surprisingly, many studies have shown a significantly higher rate of perioperative complications in morbidly obese patients. 15,26,27 Recent advances in anesthetic and surgical management, however, have made PLF an increasingly viable and safe option for morbidly obese patients, and the rate of spinal surgery in this patient population has risen in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one patient in the RA-MIS group underwent postoperative expansion surgery compared with none in the RA-OS group. This may be related to wound infection caused by the patient's second-degree obesity (BMI = 31.25) [5].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing frequency of spine surgery for patients with morbid obesity, it is important to elucidate appropriate treatment practices to reduce the risk of iatrogenic injury. Bariatric security straps can comfortably control a large abdominal pannus on the Jackson table, allowing for passage of fluoroscopy ( Elgafy et al, 2016 ). Although they were not used in this case, bariatric straps may relieve additional pressure on the anterior spine for such patients, reducing the risk of perioperative complication.…”
Section: Discussionmentioning
confidence: 99%